Outcomes of carcinoma ex pleomorphic adenoma compared to de novo adenocarcinoma of major salivary glands. Issue 2 (4th November 2020) - Patel, Evan J.; Oliver, Jamie R.; Liu, Cheng; Tam, Moses; Givi, Babak
Abstract: Background and Objectives: Carcinoma ex pleomorphic adenoma (CXPA) is a rare disease of the major salivary glands that remains poorly characterized. Our objective was to compare the clinical outcomes of patients with CXPA of the major salivary glands to those with de novo adenocarcinomas. Methods: Review of the NCDB between 2004 and 2016 to compare cases of CXPA and adenocarcinoma of major salivary glands. Demographics, clinical characteristics, and survival were analyzed. Results: We identified 1181 patients with CXPA and 3326 patients with adenocarcinoma of major salivary glands. Adenocarcinomas presented with higher rates of nodal metastasis (54.7% vs. 30.4%, p < .001). Five‐year survival of adenocarcinoma (55.8%) was worse than that of CXPA (68.5%, p < .001). When stratified by nodal status, there was no significant difference in 5‐year survival between CXPA and adenocarcinoma node‐negative (75.3% vs. 71.6%, respectively) and node‐positive (40.4% vs. 36.1%, respectively) patients. Conclusions: CXPAs of the major salivary glands present at an earlier stage with lower rates of regional metastasis compared to adenocarcinomas. After controlling for lymph node metastases, the outcomes are quite similar.